2019
DOI: 10.1007/s11205-019-02195-9
|View full text |Cite
|
Sign up to set email alerts
|

The Ambivalent Appraisal of Job Demands and the Moderating Role of Job Control and Social Support for Burnout and Job Satisfaction

Abstract: Within an extended challenge-hindrance framework, it is assumed that job demands are subjectively appraised both as challenges (that is, as working conditions that are associated with potential personal gains) and hindrances (as working conditions associated with constrains) at the same time. In accordance with transactional stress theory, the association between demand intensity and work-related attitudes (work satisfaction) and psychological strain (burnout) is expected to be mediated by individual appraisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…Thirdly, this research empirically addressed different types of job demands as they are perceived by the employees (Gerich & Weber, 2020). This could be extended in future research to examine other dimensions of job demands.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thirdly, this research empirically addressed different types of job demands as they are perceived by the employees (Gerich & Weber, 2020). This could be extended in future research to examine other dimensions of job demands.…”
Section: Discussionmentioning
confidence: 95%
“…The nonsignificant relationship might be attributed to the characteristics of the sample or suppression process (Shrout & Bolger, 2002). Such suppression factors can be task-related and organizational characteristics as boundary conditions that affect how employees appraise specific job demands (Gerich & Weber, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High work demands, low control over the work process and lack of social support significantly influence satisfaction ( 21 , 29 - 30 ) . A study on the interaction of the psychosocial factors with the Burnout dimensions showed that the psychological demand was the one most related to emotional exhaustion, while control over the work process was more associated with depersonalization and personal fulfillment ( 31 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, between the different organizational factors, perceptions of job control seem to clearly help employees to experience positive responses, work outcomes, attitudes, and satisfaction [9][10][11].…”
Section: Introductionmentioning
confidence: 99%